Pembentukan Karakter Profil Pelajar Pancasila Melalui Implementasi Kurikulum Merdeka di MAN 1 Mataram - Hadi, Lalu Sirajul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
National character reflects civilization and culture as a symbol of identity, education is an instrument to form the integrity of national identity. The implementation of the Independent Curriculum is an effort to shape the character of students into individuals who are devout, independent, cooperative, globally diverse, critical thinkers, and creative. This research examines the implementation of the Independent Curriculum in shaping students' character through habituation. The purpose of this research is to examine the effectiveness of the implementation of the Independent Curriculum in character formation of students. This research uses a qualitative approach with a descriptive research type. Data collection techniques used include observation, interviews, and documentation. Data analysis techniques are carried out through data reduction, data presentation, and drawing conclusions. The results of the research show that character formation is very effective through the strategy of habituating attitudes, activities, and rules that serve as references in the school environment. Character is also formed through the example of teachers as role models for students. The conclusion of this research is that the implementation of the Independent Curriculum can significantly shape students' character through habituation and exemplary behavior. The implications of this research emphasize the importance of the role of schools and teachers in shaping students' character with integrity.